2020
DOI: 10.1038/s41598-020-61295-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel HDAC11 inhibitors suppress lung adenocarcinoma stem cell self-renewal and overcome drug resistance by suppressing Sox2

Abstract: Non-small cell lung cancer (NSCLC) is known to have poor patient outcomes due to development of resistance to chemotherapy agents and the EGFR inhibitors, which results in recurrence of highly aggressive lung tumors. Even with recent success in immunotherapy using the checkpoint inhibitors, additional investigations are essential to identify novel therapeutic strategies for efficacious treatment for NSCLC. Our finding that high levels of histone deacetylase 11 (HDAC11) in human lung tumor tissues correlate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 68 publications
(106 reference statements)
1
31
0
Order By: Relevance
“…The same is again supported by our in vitro results, disclosing an upregulation of some HDAC isoforms in NCCIT-R, compared to NCCIT-P, both at the mRNA and protein level ( Figure 3 ). The differential expression of HDAC11 is particularly interesting and deserves to be explored in further studies, given the recently reported effect of HDAC11-specific inhibitors in eliminating treatment-resistant lung adenocarcinoma cells by targeting SOX2 [ 47 ], which is amplified in the NCCIT cell line [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same is again supported by our in vitro results, disclosing an upregulation of some HDAC isoforms in NCCIT-R, compared to NCCIT-P, both at the mRNA and protein level ( Figure 3 ). The differential expression of HDAC11 is particularly interesting and deserves to be explored in further studies, given the recently reported effect of HDAC11-specific inhibitors in eliminating treatment-resistant lung adenocarcinoma cells by targeting SOX2 [ 47 ], which is amplified in the NCCIT cell line [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…One important mechanism is that SOX2 expression in cancer cells is associated with a CSC state, which is defined as a subpopulation cells within the tumor that are shown to be more resistant toward cancer therapies. 154,241,242 For example, the tamoxifen-resistant breast cancer cells exhibit stem cell-like features with a high SOX2 level, and SOX2 knockdown restores the sensitivity toward tamoxifen, whereas SOX2 overexpression confers tamoxifen resistance. 243 Importantly, our recent study showed that MLN4924, a small molecular inhibitor of protein neddylation, 51 sensitizes otherwise resistant breast cancer cells to tamoxifen by downregulating SOX2 through inactivation of FBXW2 E3 ligase.…”
Section: Role In Drug Resistancementioning
confidence: 99%
“…Interestingly, HDAC11 was the most highly induced HDAC in response to a variety of HDAC inhibitors in AML cells, suggesting it indeed may have unique and critical properties compared to other HDAC family members ( 135 ). HDAC11 inhibition has been suggested to overcome therapy resistance in lung cancer models, and while its role in resistance to targeted therapies such as approved JAK2 inhibitors in MPN is unknown, current data suggest potential for the combination of JAK2 inhibition and HDAC11 inhibition as a possible future therapeutic strategy ( 136 ).…”
Section: Epigenetic Regulator-mediated Control Of Metabolic Processesmentioning
confidence: 99%